Abortion legalization in Uruguay: Effects on adolescent fertility - Wanda Cabella; Cecilia Velázquez (Universidad Nacional de La Plata, Centro de Estudios Distributivos, Laborales y Sociales (CEDLAS), 2022)
The Latin America and the Caribbean adolescent fertility rate is among the highest in the world: about 1.7 million children are born to teen mothers every year, and most of them are declared as being unintended pregnancies. The region also has the highest rate of unintended pregnancy of any world region, and nearly half of such pregnancies end in abortion. However, fewer than 18% of the region's women live in countries where abortion is broadly legal. This paper estimates the causal effect of abortion legalization on adolescent fertility in Uruguay, using official data on legal abortions provided after the 2012 reform. We employed a difference-in-differences strategy, classifying states by whether they are responsive or unresponsive to the reform. The results suggest that abortion reform had a negative impact on the adolescent birth rate by 2.5 to 2.8 births per thousand adolescents aged 15-19 (4% decrease from the preintervention average). Additionally, we exploited variation in reform implementation intensity through the estimation of fixed-effect linear regression models and found consistent results. Our findings are robust to controlling for a concurrent large-scale program of contraceptive implants. We conclude that legislation aimed at enhancing rights and reducing avoidable deaths and complications from unsafe abortions may also have spillover effects that help reduce adolescent fertility.
Keywords: J13; 330